2016
DOI: 10.1159/000442967
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Function in Infants with Bronchopulmonary Dysplasia: Association with Respiratory Sequelae

Abstract: Background: While cor pulmonale has been noted in infants with bronchopulmonary dysplasia (BPD), information on right ventricular (RV) function is limited. Objective: To assess RV function in infants with severe BPD and ascertain correlation with respiratory outcomes. Methods: We prospectively assessed RV function using tissue Doppler imaging (TDI), 2D fractional area change (FAC), M-mode tricuspid annular plane systolic excursion (TAPSE) and myocardial performance index (MPI) using echocardiography. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
1
37
1
Order By: Relevance
“…A recent prospective study using vascular ultrasound noted increased arterial (aorta) wall thickness and stiffness in this population (Sehgal et al. ,b,c). Its effects on the hypertrophy of the heart and reduced function consequent to increased afterload, and its likely contribution to BPD pathophysiology by way of pulmonary venous congestion has also been commented on in premature infants with BPD (Mourani et al.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…A recent prospective study using vascular ultrasound noted increased arterial (aorta) wall thickness and stiffness in this population (Sehgal et al. ,b,c). Its effects on the hypertrophy of the heart and reduced function consequent to increased afterload, and its likely contribution to BPD pathophysiology by way of pulmonary venous congestion has also been commented on in premature infants with BPD (Mourani et al.…”
Section: Introductionmentioning
confidence: 76%
“… and Sehgal et al. ,b,c). This previously published model, summarized in Figure , focused on the adjunctive role of back pressure changes from the altered systemic vasculature; LV hypertrophy, diastolic dysfunction, and raised LV end‐diastolic pressure, mediate this constellation of events (Sehgal et al.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Knowledge of right ventricular function and pulmonary arterial circulation and its affinity with airway obstruction and lung function after extremely preterm birth is limited. Previous studies in infancy have reported increasingly impaired right ventricular function in relation to prolonged duration of respiratory support in extremely preterm infants with severe bronchopulmonary dysplasia (BPD) . BPD is known to contribute to elevated pulmonary arterial vascular resistance in infancy, and if this should persist, it may induce long‐standing changes in the right ventricular geometry, structure, and function .…”
Section: Introductionmentioning
confidence: 99%